PENGARUH PROGRAM SERTIFIKASI DAN KOMPETENSI GURU TERHADAP KINERJA GURU - Franky Franky; Rachima Savira (KELOLA: Jurnal Ilmiah Manajemen, 2021)
This study aims to determine the effect of the Teacher Certification Program and Teacher Competence on Teacher Performance in SMP Negeri Kebon Jeruk District, West Jakarta City. The research method used is a quantitative method with a verification research approach and uses a qualitative associative paradigm. The sample was taken using proportionate stratified random sampling technique of 74 teachers from a population of 277 teachers, while the research data collection instrument for each variable was using a questionnaire. The results of the research analysis obtained were that the influence between the Teacher Certification Program (X1) and Teacher Competence (X2) with Teacher Performance (Y) had a Pearson product moment correlation figure of 0.798 or 63.7% which was shown in the regression equation Ŷ = 8.818 + 0.152 X1 + 0.734 X2. The coefficient of determination of 0.798 indicates that the Teacher Certification Program (X1) and Teacher Competence (X2) contributed 63.7% to Teacher Performance (Y) in SMP Negeri Kebon Jeruk District, West Jakarta City.